Pengaruh Tekanan Kerja, Stres Kerja, Kesehatan Mental Terhadap Kinerja Kariawan Perusahaan Distributor di Lombok Timur - M. Abyan Naji Asri; M. Syahru Ramdani; Ahmad Patoni; Nuro Sholihah; Ririn Apriliani (Universitas Hamzanwadi, 2024)
The distribution sector is characterized by dynamic work with high physical and mental demands, so employee performance is potentially influenced by psychological conditions during work. This study aims to analyze the influence of work pressure, job stress, and mental health on employee performance at a distribution company in East Lombok Regency. The study used a quantitative approach with an explanatory research method. Data were collected through closed questionnaires distributed to 109 employees selected using a purposive sampling technique. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS version 25. The results showed that simultaneously, work pressure, job stress, and mental health significantly influenced employee performance. Partially, work pressure did not significantly influence performance, indicating that work pressure was still within tolerable limits. Conversely, work stress had a negative and significant effect on employee performance, while mental health had a positive and significant effect. These findings indicate that psychological conditions, especially job stress and mental health, play a significant role in determining employee performance. Therefore, companies need to focus on managing job stress and efforts to maintain employee mental health to improve performance sustainably